Dissipation without resistance: Imaging impurities at quantum Hall edges - Gu Zhang; Igor V. Gornyi; Alexander D. Mirlin (Physical Review Research, 2020)
Motivated by a recent experiment [A. Marguerite et al., Nature (London) 575, 628 (2019)NATUAS0028-083610.1038/s41586-019-1704-3] on imaging in graphene samples, we investigate theoretically the dissipation induced by resonant impurities in the quantum Hall regime. The impurity-induced forward scattering of electrons at quantum Hall edges leads to an enhanced phonon emission, which reaches its maximum when the impurity state is tuned to resonance by a scanning tip voltage. Our analysis of the effect of the tip potential on the dissipation reveals peculiar thermal rings around the impurities, consistent with experimental observations. Remarkably, this impurity-induced dissipation reveals nontrivial features that are unique for chiral one-dimensional systems such as quantum Hall edges. First, the dissipation is not accompanied by the generation of resistance. Second, this type of dissipation is highly nonlocal: A single impurity induces heat transfer to phonons along the whole edge.